Pathophysiology of Age-Related Macular Degeneration: Implications for Treatment - Garcia-Garcia, Julián; Usategui-Martin, Ricardo; Sanabria, Maria Rosa; Fernandez-Perez, Esther; Telleria, Juan Jose; Coco-Martin, Rosa M. (Ophthalmic research, 2022)
Abstract Age-related macular degeneration (AMD) is a complex, multifactorial, progressive retinal disease that affects millions of people worldwide and has become the leading cause of visual impairment in developed countries. The disease etiopathogenesis is not understood fully, although many triggers and processes that lead to dysfunction and degeneration of the retinal pigment epithelium (RPE) have already been identified. Thus, the lack of cellular control of oxidative stress, altered proteostasis, dysfunction of lipid homeostasis, and mitochondrial dysfunction form an internal feedback loop that causes the RPE to fail and allows accumulation of abnormal misfolded proteins and abnormal lipids that will form drusen. An inadequate antioxidant response, deficits in autophagy mechanisms, and dysregulation of the extracellular matrix (ECM) help to increase the deposition of abnormal drusen material over time. The drusen then act as inflammatory centers that trigger chronic inflammation of the subretinal space in which microglia and recruited macrophages are also involved, and where the complement system is a key component. Choriocapillaris degeneration and nutritional influences are also classic elements recognized in the AMD pathophysiology. The genetic component of the disease is embodied in the recognition of the described risk or protective polymorphisms of some complement and ECM related genes (mainly CFH and ARMS2/HTRA1). Thus, carriers of the risk haplotype at ARMS2/HTRA1 have a higher risk of developing late AMD at a younger age. Finally, gut microbiota and epigenetics may play a role in modulating the progression to advanced AMD with the presence of local inflammatory conditions. Because of multiple implicated processes, different complex combinations of treatments will probably be the best option to obtain the best visual results; they in turn will differ depending on the type and spectrum of disease affecting individual patients or the disease stage in each patient at a specific moment. This will undoubtedly lead to personalized medicine for control and hopefully find a future cure. This necessitates the continued unraveling of all the processes involved in the pathogenesis of AMD that must be understood to devise the combinations of treatments for different concurrent or subsequent problems.